A new genus and two new species of Empoascini (Hemiptera, Cicadellidae, Typhlocybinae) from China - Qing-Ping Yao; Yan Ding; Mao-Fa Yang; Xiao-Fei Yu (ZooKeys, 2025)
A new genus and two new species of Empoascini from China are depicted in detail in this study: Singulus Yao & Yu, gen. nov., with a new species Singulus furcatus Yao & Yu, sp. nov., and Velu claustrum Yao & Yang, sp. nov. A revised key to males of Chinese species and a checklist of known species of the genus Velu are provided.